Clinical and ABCB11 profiles in Korean infants with progressive familial intrahepatic cholestasis - Park, Ji Sook (World J Gastroenterol, 2016)
AIM: To investigate clinical profiles and mutations of ABCB11 in Koreans with progressive familial intrahepatic cholestasis 2 and review the differences between Koreans and others. METHODS: Of 47 patients with neonatal cholestasis, five infants had chronic intrahepatic cholestasis with normal γ-glutamyl transpeptidase. Direct sequencing analyses of ABCB11, including exons and introns, were performed from peripheral blood. RESULTS: Living donor-liver transplantation was performed in four patients because of rapidly progressive hepatic failure and hepatocellular carcinoma. Three missense mutations were found in two patients: compound heterozygous 677C>T (S226L)/3007G>A (G1003R) and heterozygous 2296G>A (G766R). The mutations were located near and in the transmembranous space. CONCLUSION: Alterations in the transmembrane of the bile salt export pump in the Korean infants were different from those previously reported in Chinese, Japanease, Taiwanese, and European patients.